On coordination and clitic climbing in Spanish auxiliary verb constructions - Krivochen, DG; García Fernández, L (De Gruyter, 2022)
In this work we analyse some aspects of the interaction between coordination and clitic climbing in Spanish sentences with auxiliary verbs. We aim at shedding light on three kinds of structures, or ‘scenarios’: (1) those in which we find coordinated auxiliaries taking a single lexical verb as complement (Puede y debe hacerlo); (2) those in which a single auxiliary takes coordinated lexical verbs as complement (estás molestándonos y mirándonos), and (3) those in which coordinated auxiliaries take coordinated lexical verbs as complement (puede y debe terminarlo y entregarlo). Our proposal will involve a combination of Gapping and Across-the-Board rule application for Scenarios (1) and (2) and Right Node Raising for Scenario (3). We will argue that well-known syntactic constraints on long distance dependencies, such as those proposed in Ross, John Robert. 1967. Constraints on variables in syntax. Cambridge: MIT disertation, can account for the facts without the need for ad hoc machinery.